GIRLS’ EXPLOITATION IN THE TRIPLE BORDER AMONG ARGENTINA, BRASIL AND PARAGUAY: BETWEEN COLONIALISM AND HUMAN RIGHTS NARRATIVES - ZSÖGÖN, MARIA CECILIA (Society Register, 2019)
This article focuses on the narratives and underlying ideologies that enable the persistence of girls’ sexual exploitation in the region of the Triple Border among Argentina, Brasil and Paraguay, where field work was conducted. We argue that the persistence of colonial practices has contributed to the reproduction of subalternity positions for girls and women – especially from impoverished sectors – enforced by the conservative and patriarchal discourse present in many countries of the region. This scenario enables the persistence and naturalization of certain practices that became “invisible” or even accepted and justified as being “cultural”. In this sense, we propose that human rights narrative, although being a Eurocentric construction, can comprise a platform for raising issues on gender inequality and all forms of violence and exploitation taking place in the peripheral regions of the world.